Towards ferroelectric and multiferroic nanostructures and their characterisation. (22nd August 2008) - Harnagea, C.; Cojocaru, C.V.; Nechache, R.; Gautreau, O.; Rosei, F.; Pignolet, A.
We summarise here our efforts toward the fabrication and characterisation of ferroelectric and multiferroic films and structures. First, we discuss the challenges related with the fabrication and characterisation of nanostructures of functional complex oxides. In particular, to demonstrate the functionality of our films and especially of our structures, we briefly describe atomic force microscopy techniques tailored for local electrical or magnetic characterisation. Piezoresponse Force Microscopy and Magnetic Force Microscopy enable the characterisation of piezoelectric, ferroelectric and magnetic properties at the nanoscale. We then report the fabrication of various functional oxide films by Pulsed Laser Deposition (PLD), in particular the deposition of the conducting oxide electrode SrRuO3 at room temperature. We also describe the fabrication of ferroelectric BaTiO3 and BiFeO3, both in the form of film and mesoscopic (sub-micron size) islands. The formation of ferroelectric structures of arbitrary shape at controlled location was also achieved by nanostencilling, i.e., using a shadow-mask with nanoscale features. Finally, the successful synthesis of Bi2FeCrO6 films by pulsed laser deposition is then detailed; this is a new multiferroic material predicted by ab-initio calculations. The Bi2FeCrO6 films have the correct cationic stoichiometry throughout their thickness and their crystal structure is found to be very similar to that of BiFeO3. Bi2FeCrO6 films exhibit good piezoelectric and ferroelectric properties at room temperature, a property that was not predicted. Magnetic Force Microscopy reveals the presence of magnetic domains and confirms the macroscopic magnetic measurements showing that the Bi2FeCrO6 films do exhibit a saturation magnetisation about one order of magnitude higher than that of BiFeO3 films having the same thickness.